A trustworthy network or a technologically disguised scam: A biblio-morphological analysis of bitcoin and blockchain literature. Issue 6 (31st January 2020) - Issac, Abraham Cyril; Baral, Rupashree
Abstract : Purpose: The initiation of cryptocurrency such as bitcoin has invoked a general curiosity in the international financial regime. Bitcoin works in a peer-to-peer framework with no third party acting as a monitoring agency. This brings in both positive and negative spirit to the table. Though generic understanding is available, the studies done on bitcoin and blockchain are far and few. The purpose of this paper is to decipher the level of understanding the scientific world has on bitcoin and the underlying blockchain and thereby to find out the pertinent research gaps existing in this field. Design/methodology/approach: A biblio-morphological analysis is undertaken which underscores a comprehensive framework characterizing the bitcoin and blockchain literature in terms of dimensions and options. This was developed as a result of extensive scanning of the relevant literature. Findings: The biblio-morphological analysis broadly outlines the present status of the research on the topic. The morphological analysis brings out the 169 research gaps that exist in the area of bitcoin and underlying blockchain technology. The cross-consistency matrix underscores the fact that this novel technology bears large research potential. Research limitations/implications: The biggest contribution of this paper would be to underline the present status of the literature on bitcoin and blockchain technology. This study attempts to make this document a vade mecum for both the industry and the academia in the area of bitcoin and blockchain technology. The blockchain technology and its effects and influences on other disciplines can effectively be explored by taking cues from the gaps identified by this biblio-morphological analysis. Such unique combinations can open up new avenues of research in the broader realm of business and economics. Originality/value: To the best of the authors' knowledge, this is a first comprehensive biblio-morphological analysis on bitcoin and underlying blockchain technology, which characterizes blockchain literature and thereby offers to reduce redundant research by delineating the possible avenues in the area of blockchain technology.